Geological storage of CO2–N2–O2 mixtures produced by membrane‐based direct air capture (DAC). Issue 4 (1st June 2021) - Tsuji, Takeshi; Sorai, Masao; Shiga, Masashige; Fujikawa, Shigenori; Kunitake, Toyoki
Abstract: Carbon capture and storage has been considered as a realistic approach to reducing atmospheric CO2 concentrations. However, the cost of capturing high‐purity CO2 typically used for geological storage (e.g., 98%) is high. Direct air capture (DAC), a technology that extracts CO2 of relatively low‐purity from the ambient atmosphere, has been recently proposed as a means to achieve negative CO2 emissions when the product is sequestered underground. Although the CO2 produced by DAC is of low‐purity, the other gaseous components (mainly nitrogen and oxygen) are not hazardous materials like NOx and SOx that must be typically dealt with by conventional projects in coal‐burning plants. Here, we evaluate geological storage of the low‐purity CO2 captured via advanced membrane‐based DAC technology. The ubiquity of ambient air is important in reducing transport costs and ensuring social acceptance as the CO2 product can be both produced and stored at sites in remote areas, such as deserts and offshore platforms. We calculated the density of CO2 –N2 –O2 mixtures via molecular dynamics simulation and evaluated the cost of the low‐purity CO2 storage. Our evaluation suggests that the storage of low‐purity CO2 in geological formations is environmentally acceptable and economically viable. © 2021 The Authors. Greenhouse Gases: Science and Technology published by Society of Chemical Industry and John Wiley & Sons Ltd.